2018
DOI: 10.18585/inabj.v10i1.296
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Human Papillomavirus 16 and 52 L1 Gene from Cervical Cancer in Bandung, Indonesia

Abstract: BACKGROUND: Chronic infection with high-risk type of human papillomavirus (HPV) can cause cervical cancer. Previous studies showed that multiple infections of HPV are found in cervical cancer caused by multiple HPV infections and the most common are HPV-16 and HPV-52. The origin of HPV-16 circulating in Indonesia varies. The purpose of this study was to explore the origin of multiple infections of HPV-52 and HPV-16 in cervical cancer by using a phylogenetic tree.METHODS: During July-November 2010, 100 women we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…(7) Cervical cancer is the fourth most common cancer in women caused by Human Papilloma Virus (HPV), which can affect cell proliferation and apoptosis. (9) Molecular studies revealed viral oncoproteins, E6 and E7, interfere with the tumor suppressor genes p53 and pRb. Subsequently, inactivation of host proteins disrupts DNA repair and apoptosis mechanisms, and forces cells to remain in a proliferative state and exit the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Cervical cancer is the fourth most common cancer in women caused by Human Papilloma Virus (HPV), which can affect cell proliferation and apoptosis. (9) Molecular studies revealed viral oncoproteins, E6 and E7, interfere with the tumor suppressor genes p53 and pRb. Subsequently, inactivation of host proteins disrupts DNA repair and apoptosis mechanisms, and forces cells to remain in a proliferative state and exit the cell cycle.…”
Section: Introductionmentioning
confidence: 99%